2016
DOI: 10.1038/ncomms11669
|View full text |Cite
|
Sign up to set email alerts
|

Diverse genetic architectures lead to the same cryptic phenotype in a yeast cross

Abstract: Cryptic genetic variants that do not typically influence traits can interact epistatically with each other and mutations to cause unexpected phenotypes. To improve understanding of the genetic architectures and molecular mechanisms that underlie these interactions, we comprehensively dissected the genetic bases of 17 independent instances of the same cryptic colony phenotype in a yeast cross. In eight cases, the phenotype resulted from a genetic interaction between a de novo mutation and one or more cryptic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 43 publications
2
63
0
Order By: Relevance
“…Perturbation of Hsp90 was thus thought to uncover cryptic polymorphisms that do not typically show effects, thereby expanding the amount of heritable phenotypic variation in a population [1,2,47] (Fig 1A). Because of its role in buffering, Hsp90 began to be regarded as a capacitor that facilitates the accumulation of cryptic genetic variation [13,812].…”
Section: Perturbation Of Hsp90 Impacts Heritable Phenotypic Variationmentioning
confidence: 99%
“…Perturbation of Hsp90 was thus thought to uncover cryptic polymorphisms that do not typically show effects, thereby expanding the amount of heritable phenotypic variation in a population [1,2,47] (Fig 1A). Because of its role in buffering, Hsp90 began to be regarded as a capacitor that facilitates the accumulation of cryptic genetic variation [13,812].…”
Section: Perturbation Of Hsp90 Impacts Heritable Phenotypic Variationmentioning
confidence: 99%
“…However, revertants recovered from these screens typically carry multiple mutations and which mutation is the suppressor is not always clear-cut [12, 16]. A straightforward strategy to distinguish a mutation with a phenotypic effect from its co-occurring ‘passenger’ mutations is by using crosses in combination with whole genome sequencing [12, 21]. Recently, such an approach was used to identify more than 200 mutation-suppressor pairs in a single study [12].…”
Section: High-throughput Techniques For Identifying Suppressor Mutatimentioning
confidence: 99%
“…Supporting this view, crossing experiments in budding yeast indicate that most conditional essentialities are mediated by two or more genetic variants [19, 66]. More generally, work on other cases in which a mutation shows different effects across genetic backgrounds has shown that response to mutations can be mediated by higher-order sets of variants that interact not only with a mutation, but also with each other [21, 64, 6770] and potentially even the environment [68]. However, only a small number of examples of this phenomenon have been comprehensively teased apart at the genetic level [55], leaving open the possibility that other genetic architectures, such as those in which a mutation acts as a hub of pairwise genetic interactions with many different variants [7, 8], could also be important.…”
Section: The Genetic and Molecular Basis Of Naturally Occurring Genetmentioning
confidence: 99%
See 2 more Smart Citations